2022
DOI: 10.3390/app12031190
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Near-Infrared Light Propagation in Aqueous Alumina Suspensions Using the Steady-State Radiative Transfer Equation and Dependent Scattering Theory

Abstract: Understanding light propagation in liquid phantoms, such as colloidal suspensions, involves fundamental research of near-infrared optical imaging and spectroscopy for biological tissues. Our objective is to numerically investigate light propagation in the alumina colloidal suspensions with the mean alumina particle diameter of 55 nm at the volume fraction range 1–20%. We calculated the light scattering properties using the dependent scattering theory (DST) on a length scale comparable to the optical wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We preliminary confirmed that the PDE results agree with the RTE results at most spatial regions, especially inside the medium for the two suspensions. For the alumina suspension, please see our previous study [49] . We numerically calculated the PDE using the finite difference method with the spatial grid size of 0.04 cm for a cubic heterogeneous medium with a size of 5.2 cm.…”
Section: Modeling Initial Photoacoustic Pressure Based On a Multi-sca...mentioning
confidence: 99%
“…We preliminary confirmed that the PDE results agree with the RTE results at most spatial regions, especially inside the medium for the two suspensions. For the alumina suspension, please see our previous study [49] . We numerically calculated the PDE using the finite difference method with the spatial grid size of 0.04 cm for a cubic heterogeneous medium with a size of 5.2 cm.…”
Section: Modeling Initial Photoacoustic Pressure Based On a Multi-sca...mentioning
confidence: 99%